Embedded Pork Bone Causing Esophageal Perforation and an Esophagus-Innominate Artery Fistula - Andrew C. Berry; Peter V. Draganov; Brijesh B. Patel; Danny Avalos; Warren L. Reuther; Avinash Ravilla; Bruce B. Berry; Michael J. Monzel (Case Reports in Gastrointestinal Medicine)
Chronically embedded foreign bodies can lead to perforations, mediastinitis, and abscess, amongst a host of other complications. A 20-year-old mentally challenged female presented with “something stuck in her throat,” severe dysphagia, and recurrent vomiting. Initial imaging was unremarkable; however, subsequent imaging and esophagogastroduodenoscopy two weeks later revealed an embedded pork bone. Surgery was performed to remove the bone and fix the subsequent esophageal perforation and esophagus-innominate artery fistula. This case helps reinforce the urgency in removing an ingested foreign body and the ramifications that may arise with chronically embedded foreign bodies.